Battery electric vehicles: What is the minimum range required?. (1st January 2019) - Shi, Xiao; Pan, Jian; Wang, Hewu; Cai, Hua
Abstract: Identifying the battery range needs at the individual level is critical to enhance our understanding of the environmental benefits and electricity grid load impacts from large-scale battery electric vehicle (BEV) adoption, and inform policy decision making for charging infrastructure development and BEV system deployment. However, two research gaps exist in existing research: neglecting the use of public charging stations and lacking a model to identify the minimum battery ranges required to fulfill all the travel demands of a vehicle at the individual level. This study fills these gaps by developing an optimization model to identify the minimum required BEV battery ranges at the individual level, using real world vehicle travel data and charging station location information. Based on our case study of taxis and private vehicles in Beijing, China, the results show that: 1) with home charging and the existing public charging infrastructure, it is feasible to use existing BEV models to replace a significant portion of gasoline vehicles without sacrificing individual mobility needs; 2) battery technologies are unlikely to be the major bottleneck to BEV adoption; and 3) increase the service range of charging infrastructures can reduce the minimum required battery ranges, but function substitutions will need to be considered. Highlights: An optimization model is proposed to identify the minimum battery range needs. Case study uses real-world travel data and charging infrastructure in Beijing. 77% of the vehicles can use currently available BEV models to meet all travel needs. Increasing charging station service range can reduce the battery range needs. Considering function substitution is key to increase charging station service range.